Analisis Kelayakan Bisnis Water Park di Pulau Bintan [Business Feasibility Analysis of a Water Park on Bintan Island] - Yustisia Kristiana; Jacqueline Lawrence (DeReMa (Development Research of Management): Jurnal Manajemen, 2019)
Bintan Regency is one of the districts in the Riau Islands which relies on the tourism sector as the main sector. The geographical position close to Singapore is a force in capturing foreign tourists. This has resulted in an increase in the number of tourist visits, especially foreign tourists. Bintan Regency is rich in natural and cultural tourism but is still lacking for man-made tourism. Diversity of tourist attraction can be a reason for tourists to extend their length of stay. This raises opportunities to open a water park business. The purpose of this paper is to examine business feasibility by analyzing market aspects market and marketing aspects, technical aspects, management and organizational aspects, and financial aspects of the water park business. The research method used is descriptive research method. Data collection was carried out by distributing questionnaires to 222 respondents using convenience sampling, observation, and interview techniques. The analytical method carried out consists of several aspects, i.e. market and marketing aspects, technical aspects, management and organizational aspects, and financial aspects. Based on the results of the analysis of the four aspects, the water park business plan is feasible.Bahasa Indonesia Abstrak: Kabupaten Bintan adalah merupakan salah satu kabupaten di Kepulauan Riau yang mengandalkan sektor pariwisata sebagai sektor utama. Posisi geografis yang dekat dengan Singapura menjadi kekuatan dalam menjaring wisatawan mancanegara. Hal ini berdampak pada peningkatan jumlah kunjungan wisatawan, khususnya wisatawan mancanegara. Kabupaten Bintan kaya akan wisata alam dan budaya namun masih kurang untuk wisata buatan. Keanekaragaman daya tarik wisata dapat menjadi alasan wisatawan untuk memperpanjang lama tinggalnya. Ini memunculkan peluang untuk membuka bisnis water park. Tujuan dari penulisan ini adalah untuk menguji kelayakan bisnis dengan menganalisis aspek pasar dan pemasaran, aspek teknis, aspek manajemen dan organisasi, serta aspek finansial dari bisnis water park. Metode penelitian yang digunakan adalah metode penelitian deskriptif. Proses pengambilan data dilakukan dengan cara penyebaran kuesioner kepada 222 responden menggunakan teknik convenience sampling, observasi, dan wawancara. Metode analisis yang dilakukan terdiri dari beberapa aspek, yaitu aspek pasar dan pemasaran, aspek teknis, aspek manajemen dan organisasi, dan aspek finansial. Berdasarkan hasil analisis terhadap keempat aspek maka rencana bisnis water park ini layak untuk dijalankan.